Differences in Estimates of Minimum Dietary Diversity by Using the New and Old Definition: Evidence From Bangladesh - Roy, Abhijeet (Curr Dev Nutr, 2021)
OBJECTIVES: Minimum Dietary Diversity (MDD) is an indicator to assess feeding practices of children aged 6–23 months. The WHO and UNICEF have recently revised the definition of MDD, replacing ‘≥4 out of 7 food groups (MDD-7FG)’ with ‘≥5 out of 8 food groups (MDD-8FG)’. In the new definition, breast milk was considered as a separate food group. We aimed to estimate the implications of this change on the prevalence of MDD at the national and regional levels of Bangladesh. METHODS: We analyzed data from the national food security and nutrition surveillance round 2018–2019. MDD was defined and calculated according to the WHO-UNICEF guidelines. The prevalence of MDD-7FG and MDD-8FG was estimated and stratified by gender, age groups, place of residence, division, and wealth index. The difference between the prevalence between MDD-7FG and MDD-8FG was presented as percentages. RESULTS: Compared to the older definition, the overall prevalence of MDD was lower among 6 to 23 months old children in Bangladesh (46.2% vs. 54.7%). The absolute percentage point difference between the estimates (MDD-8FG vs. MDD-7FG) was higher among the boys (44.0% vs. 53.2%), 12–23 months aged old children (53.4% vs. 63.4%), children living in the non-slum urban areas (30.2% vs. 42.4%) and Dhaka division (42.0% vs. 56.3%), and among the children of middle-class families (40.3% vs. 57.6%). CONCLUSIONS: The new definition and the inclusion of breast milk intake as a new food group led to a decrease in the prevalence of minimum dietary diversity in Bangladesh. The country program needs to emphasize the continuation of breastfeeding until two years of age of the children. Moreover, the changes in the definition of MDD and the resultant consequence should be kept in mind while performing trend analysis of dietary diversity in Bangladesh and elsewhere. FUNDING SOURCES: Ministry of Health and Family Welfare, Government of Bangladesh.